2019
DOI: 10.1101/521237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meiotic viral attenuation through an ancestral apoptotic pathway

Abstract: The programmed release of apoptogenic proteins from mitochondria is a core event of apoptosis, though ancestral roles of this phenomenon are not known. In mammals, one such apoptogenic protein is Endonuclease G (EndoG), a conserved nuclease that fragments the DNA of dying cells.In this work, we show that budding yeast executes meiotically programmed mitochondrial release of an EndoG homologue, Nuc1, during sporulation. In contrast to EndoG's ostensible pro-death function during apoptosis, Nuc1 mitochondrial re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…These images revealed L-A dsRNA to accumulate in foci, reminiscent of "viral factory" sites of viral replication observed in human cells (Fig 1B and S1) 26 . Consistent with previous findings in other strain backgrounds, western blotting showed that Gag protein levels were elevated in nuc1∆ and ski3∆ mutants 12,18,27 , and we determined that nuc1∆ ski3∆ double mutants accumulated massively elevated Gag levels, confirming that NUC1 and SKI3 participate in separate antiviral pathways (Fig 2A).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…These images revealed L-A dsRNA to accumulate in foci, reminiscent of "viral factory" sites of viral replication observed in human cells (Fig 1B and S1) 26 . Consistent with previous findings in other strain backgrounds, western blotting showed that Gag protein levels were elevated in nuc1∆ and ski3∆ mutants 12,18,27 , and we determined that nuc1∆ ski3∆ double mutants accumulated massively elevated Gag levels, confirming that NUC1 and SKI3 participate in separate antiviral pathways (Fig 2A).…”
supporting
confidence: 92%
“…We showed previously that L-A replication was held in check during sporulation by the mitochondrial DNA/RNA endonuclease Nuc1, a homolog of endonuclease G (EndoG) found in all eukaryotes and many prokaryotes 14 . EndoG is involved in mammalian programmed cell death that frequently occurs in virus infected cells, and programmed cell death is intrinsic to yeast sporulation [15][16][17][18] .…”
mentioning
confidence: 99%
“…autophagy, vesicle trafficking, cancer, neurodegeneration) and are ideal models for dissecting unicellular eukaryotic cell death. Many Saccharomyces cerevisiae genes have been reported to promote or inhibit death (Chaves et al, 2021), some with semblances to mammals (Fannjiang et al, 2004;Gao et al, 2019;Ivanovska and Hardwick, 2005). A common theme shared by the four bestcharacterized mammalian cell death pathways is membrane permeabilization carried out by pore-forming proteins such as BAX (apoptosis), MLKL (necroptosis), and gasdermins (pyroptosis), or by lipid peroxidation (ferroptosis), which typically mark a commitment or final step to cell death.…”
Section: Introductionmentioning
confidence: 99%
“…The high variation in the sporulation efficiency of yeast carrying a virus could be determined by viral load, which plausibly influences host metabolic costs of endosymbiosis. Though not explored in this paper, the degree of coadaptation likely affects whether hosts have evolved stabilizing mechanisms, such as sanctions of viral load (Gao, Chau, Chowdhury, et al, 2019; Wickner & Edskes, 2015), in order to compensate for the metabolic costs of endosymbiosis.…”
Section: Discussionmentioning
confidence: 99%